1998
DOI: 10.1063/1.121746
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy mobility determined from current measurements in thin Ba0.5Sr0.5TiO3 films

Abstract: The current density is measured as a function of time for thin (⩽1000 Å) barium strontium titanate (BST) capacitors with platinum electrodes. The current density curve shows a peak prior to the onset of resistance degradation. The peak position on the time axis varies with applied voltage and temperature. The data are explained by the theory for space-charge-limited (SCL) current transients, and the measured current is identified as ionic current associated with oxygen vacancies. Using the SCL analysis, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(90 citation statements)
references
References 17 publications
8
80
1
Order By: Relevance
“…In addition, BST thin films show a remarkable dielectric relaxation phenomenon that strongly affects the dielectric properties of the films. 8 Many researches have reported the effect of the postannealing treatment under an O 2 and/or N 2 atmosphere in the behavior of BST film leakage currents. Joo et al 6 have reported oxygen vacancies in BST films, obtained by the sputtering technique, that are usually generated during the production of Pt/BST/Pt capacitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BST thin films show a remarkable dielectric relaxation phenomenon that strongly affects the dielectric properties of the films. 8 Many researches have reported the effect of the postannealing treatment under an O 2 and/or N 2 atmosphere in the behavior of BST film leakage currents. Joo et al 6 have reported oxygen vacancies in BST films, obtained by the sputtering technique, that are usually generated during the production of Pt/BST/Pt capacitors.…”
mentioning
confidence: 99%
“…These vacancies are responsible for the higher leakage currents of BST films, as well as for the degradation of dielectric properties. [7][8][9] Moreover, some recent studies have revealed that electron trapping in thin films induces a voltage offset in the polarizationvoltage characteristics. 10 This letter investigates the influence of postannealing treatments on the dielectric properties of BST thin films, after top electrode deposition, in oxygen and nitrogen atmospheres.…”
mentioning
confidence: 99%
“…Moreover, one notes that the time constant r τ , which reflects the mobility of a certain type of charge defects responding to the external stimulus, can be used to distinguish the nature of charged defects. 13,31 Having carefully examined the results in Figure 3c, we note that peak frequencies of I and II are located below 10 Hz at room temperature. Therefore, the corresponding time constants are estimated to be >0.01 s, which is comparable to the values for V O reported in the previous work.…”
Section: +mentioning
confidence: 99%
“…We assume here, from drift mobility data on 100 nm-thick BST films (Zafar et al, 1998) The particular initial-boundary value problem includes the following boundary conditions, corresponding to shorted or ground electrodes at the film boundaries, which themselves are constrained to remain impenetrable to vacancy flow:…”
Section: Sample Problem-bst Filmmentioning
confidence: 99%